Pendampingan Pembuatan Laporan Keuangan Sederhana Pada Usaha Roti Home Made - Paulina Rosna Dewi Redjo; Marce Sherly Kase; Anggelina Delfiana Klau (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Community service activities carried out are in the form of assistance for UMKM "home made bread business" in terms of managing finances using accounting standards. The mentoring program offered is in the form of 1) simple financial management training for home made bread business owners.